Research Trends and Hotspots on Herpes Zoster: A 10-Year Bibliometric Analysis (2012–2021) - Zhang, Jian; Han, Xu; Su, Diansan; Gu, Xiyao; Yu, Weifeng (Frontiers in Medicine, 2022)
Purpose Herpes zoster infection, with its considerable burden to individuals and society, remains a challenge around the world. However, to the knowledge of the authors, little bibliometric quantitative or qualitative analysis has been carried out to evaluate herpes zoster research. This study aimed to use a bibliometric analysis to evaluate current publication trends and hotspots on herpes zoster research worldwide, in order to advance research in this field. Methods Relevant publications from January 2012 to December 2021 were collected from the Web of Science Core Collection database. Citespace (V5.8.R3) was used to analyze the research points, including publication countries, institutions and authors, cited author, cited reference and their clustering, and keyword co-occurrence, and burst keyword to acquire research trends and hotspots. Results A total of 9,259 publications were obtained, with a steady increase in the number of annual publications during the decade. Articles were the main type of publication. The United States is the leading country in this research, and the University of Colorado has the highest influence in this field. Oxman is the most representative author, with a main research interest in herpes zoster vaccines. The top five cited authors' publications focused on herpes zoster vaccines, molecular mechanisms, and postherpetic neuralgia. A co-citation map resulted 19 main clusters, and revealed that vaccines, postherpetic neuralgia, treatments, varicella zoster virus and its mechanisms, and epidemiology of herpes zoster were the current research focus after clustering co-cited publications. Human herpesviruses, antiviral prophylaxis, rheumatoid arthritis, recombinant zoster vaccine, varicella vaccination and postherpetic neuralgia were the top clusters after co-occurrence keywords analysis. Moreover, burst keywords detection showed that the subunit vaccine was the new hotspot in the field of herpes zoster. Conclusion This bibliometric study defined the overall prospects in the field of herpes zoster and provided valuable instruction for the ongoing research. The keyword “subunit vaccine” indicated that a vaccine for herpes zoster prevention was the hotspot. Efforts to prevent varicella zoster virus infection will be essential to improve herpes zoster outcomes.